Surface Roughness Evolution Model for Finishing Using an Abrasive Tool on a Robot. (3rd September 2015) - Fernandez, Angel; Jose Antonio, Dieste; Javierre, Carlos; Jorge, Santolaria
The polishing process is the final step in the manufacturing workflow for many parts and tools. While previous tasks have evolved technically, the finishing of freeform surfaces is still effected mostly by hand. Many parts are rejected because no control of the process is possible. The main problems are geometrical shape deviations and no repeatability of the process. A new methodology has been developed for the passes of the abrasive on the polished part. This research focusses on the feasibility of robotic polishing and the development of a new evolution model pertaining to the surface roughness for an abrasive tool mounted on a spherical robot. The polishing principle is mechanic and based on dry friction. The tool is multilayered with a compressive foamed core. The combination of rotational and translational movement requires the creation of a model that can predict the footprint on the polished surface. The mathematical model developed for the evolution model permits for making a prediction of the final surface quality in the function of the programmed polishing parameters. Furthermore, the model described allows for setting up polishing parameters in order to reach a desired final roughness with less than 15% deviation. Repeatability is assured and polishing time is reduced down to 1/5 of manually effected procedures.